(untitled) (Al-Academy, 2016)
The design fabrics of the most important episodes that are at the core process rhetorical communication, until they became these episodes ample room for research and investigation, and the issue of non-familiar formality is nothing but the result of those relationships Constructivism, which is the result of an effort builders coherent activate the shape and attributes of phenotypic, therefore it will cause him a lot of questions about his and founded the organization in order to activate the speech communication between the product(cloth)and the receiver .On this basis, the research problem identified on imposing the question follows:1. Does the non-familiar formal role in enriching communication discourse of women’s fabric designs?2. Are there foundations of design to enrich the speech communication through the form of others familiar? The research aims to disclose the role of non-formal unfamiliar to the enrichment of the speech communication designs for women’s fabrics, design and developfoundationsforpracticalpurposestoenrichthespeechcommunicationthroughnon-formal familiar to women’s fabric designs.In regard to the second quarter, which contained the theoretical frame work and previous studies, it was included in the board three sections, the first non-familiar in art and design, and the second placed structural elements in the design of cloth women, and the third concerned with the concept of speech communication in the design. Third chapter has dealt with procedures search. Fourth chapter search results and conclusions among the most important:1- The method abstract method mostly as a technical wizards out new designs far from copying and imitation.2 - Most of the designs focused on technology and reduction deletion and addition, forms and design vocabulary, which has worked to change the phenotypic traits formal vocabulary. Researcher and put the most important cornerstones of design to enrich the communication through speech form is not uncommon in women’s fabrics and designs as follows:1 – rely on abstract art ,as away to form an unfamiliar configurations according to a new vision of contemporary creativity in the field of technical configuration